A One-Health Approach to Investigating an Outbreak of Alimentary Tick-Borne Encephalitis in a Non-endemic Area in France (Ain, Eastern France): A Longitudinal Serological Study in Livestock, Detection in Ticks, and the First Tick-Borne Encephalitis Virus Isolation and Molecular Characterisation - Gonzalez, Gaëlle; Bournez, Laure; Moraes, Rayane Amaral; Marine, Dumarest; Galon, Clémence; Vorimore, Fabien; Cochin, Maxime; Nougairède, Antoine; Hennechart-Collette, Catherine; Perelle, Sylvie; Leparc-Goffart, Isabelle; Durand, Guillaume André; et al. (Frontiers in Microbiology, 2022)
Tick-borne encephalitis virus’ (TBEV) geographic range and the human incidence are increasing throughout Europe, putting a number of non-endemic regions and countries at risk of outbreaks. In spring 2020, there was an outbreak of tick-born encephalitis (TBE) in Ain, Eastern France, where the virus had never been detected before. All patients but one had consumed traditional unpasteurised raw goat cheese from a local producer. We conducted an investigation in the suspected farm using an integrative One Health approach. Our methodology included (i) the detection of virus in cheese and milk products, (ii) serological testing of all animals in the suspected farm and surrounding farms, (iii) an analysis of the landscape and localisation of wooded area, (iv) the capture of questing ticks and small mammals for virus detection and estimating enzootic hazard, and (v) virus isolation and genome sequencing. This approach allowed us to confirm the alimentary origin of the TBE outbreak and witness in real-time the seroconversion of recently exposed individuals and excretion of virus in goat milk. In addition, we identified a wooded focus area where and around which there is a risk of TBEV exposure. We provide the first TBEV isolate responsible for the first alimentary-transmitted TBE in France, obtained its full-length genome sequence, and found that it belongs to the European subtype of TBEV. TBEV is now a notifiable human disease in France, which should facilitate surveillance of its incidence and distribution throughout France.